Interpersonal factors of human social networks - SILVA JÚNIOR, Mauro Dias (Universidade Federal do Pará, 2020)
According to the Social Brain Hypothesis (S.B. H.), social networks are a specific level of analysis of social behavior in which the individual on spot has a set of social contacts, with whom he/she interacts regularly and consistently, and with whom he/she exchanges personal information. Although, H.C.S. and other theoretical perspectives are engaged to investigate a similar set of variables on social networks, this similarity did not lead to a consensus on the definition of this term. Given this theoretical and methodological diversity, we conducted three studies in order to elucidate this phenomenon, since the available instruments can so far not be accurate enough to define it accurately. Thus, we discuss and propose that these variables can be understood as three types of interpersonal factors (factors of the Ego, the Alter, and Context). The presence/ absence of each of these categories produces a unique setting in social networks, which, however, it seems to have a common bias on the peculiar way humans to bond and establish interpersonal relationships. This underlying nature is considered human psychology, or the "Ego", an unconscious agent who actively choose their social contacts and decide how to invest his/her time and bonding. This "Ego" has a neural basis, particularly the neocortex, whose volume is correlated with the size of human and non-human social groups. We also examined how the "Ego" shows a distinct preference for maternal relatives over other types of relatives. This preference changes according to individuals’ lifespan, but on the other hand was less sensitive to cultural aspects. Finally, we found that the higher/lower frequency of relatives and friends in social networks depends on the order in which thexii section of each social group is presented in the questionnaires. Furthermore, the listing order in which participants described their social contacts depended on the emotional closeness to each social contact. We concluded that methodological decisions can affect the way we define the networks size and composition, and therefore, improvements are required to define the concept of social networks more accurately. The set of results was interpreted according to the S.B.H. and the Evolutionary Psychology, which both understand this psychological agent as a product of evolution, which interacts with the current environment, the features that were selected in the evolutionary past of our species.